The Website Application for Distribution, Acceptance of Zakat, Alms, Infaq, and Endowments LAZISMU UHAMKA - Estu Sinduningrum; Muchammad Sholeh; Siti Mindesih (UHAMKA Press, 2023)
Web-based application is a system that is packaged in web technology (2.0) along with the development of digital transformation which can be accessed via a web browser or mobile browser on a smartphone. The development of this web-based IT system that will be used is the LazisMU Uhamka system. Currently the LazisMU system is still operated manually, from input, process and output. With the development of the system, where LazisMU will adopt using web technology with a research methodology approach Feature-Driven Development (FDD) which is part of the agile methodology where the focus is on customer experience, iterative, and incremental which is very suitable in building the system. Overall, by building a web-based application through this methodology, it is possible to maximize the process of the computerized LazisMU Uhamka system. The information features of the distribution and receipt of zakat, infaq, alms, and waqf can be accessed easily according to the privileges of each user (employee) of LazisMU Uhamka. The overall results of the questionnaire from tests conducted on twenty users obtained an average value of 85% stating that this zakat information system has met the needs and is easy to understand.